Right Moves : The Conservative Think Tank in American Political Culture since 1945 - Stahl, Jason M. (Book collections on Project MUSE., 2016)
" ... Traces the progression of think tanks from the rise of a broad conservative movement and the turn away from New Deal liberalism, their expanding role in advancing a neoconservative foreign policy through U.S. military power from the 1980s onward, and their current prominence as a counterweight to progressive political institutions and thought"--